Оrganisation of engineering and technology bachelors training process for project and design activity at Tomsk Polytechnic University - Michail G. Minin; Alyona A. Zakharova; Igor A. Safyannikov; Evgeniya V. Vehter (Высшее образование в России)
The article describes the organization process for Bachelors of Engineering and Technology training for project and design activities at Tomsk Polytechnic University. There were justified organizational and pedagogical conditions for effective training of Bachelors of Engineering and Technology for future project and design activities.